2017
DOI: 10.16965/ijar.2017.401
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Drainage Pattern of Inferior Mesentric Vein

Abstract: Introduction: The inferior mesenteric vein drains blood from part of the large intestine and usually terminates in the splenic vein. It may drain into superior mesenteric vein or junction of superior mesenteric vein and splenic vein. Knowledge of such variations is very useful and important for anatomists, radiologists and surgeons performing surgeries related to this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…IMV begins as the superior rectal vein at about the mid-point of the anal canal, then passes along the inferior mesenteric artery to end in the SV. It receives blood from the superior rectal veins, the sigmoid veins and the left colic vein (Snell, 2012), (Kaur et al, 2017) In this report, we present a case of an unusual giant IMV with an anomalous insertion in the presence of cirrhosis observed during routine dissections at the Department of Anatomy, University of Peradeniya.…”
Section: Introductionmentioning
confidence: 91%
“…IMV begins as the superior rectal vein at about the mid-point of the anal canal, then passes along the inferior mesenteric artery to end in the SV. It receives blood from the superior rectal veins, the sigmoid veins and the left colic vein (Snell, 2012), (Kaur et al, 2017) In this report, we present a case of an unusual giant IMV with an anomalous insertion in the presence of cirrhosis observed during routine dissections at the Department of Anatomy, University of Peradeniya.…”
Section: Introductionmentioning
confidence: 91%
“…Anatomical references related to PV structures primarily focus on the SMV and SpV, offering limited information about the IMV, except for its common drainage into the SpV [1]. Nevertheless, recent studies have revealed that the IMV can also merge and discharge into the SMV, the junction between the SpV and SMV, or other mesenteric venous drainage regions [2,3].…”
Section: Introductionmentioning
confidence: 99%